Remixing and drawing : sources, influences, styles - Mueller, Ellen, 1982- (Routledge, 2018)
This succinct book articulates a clear framework for remixing in drawing at intermediate and advanced levels. It begins by walking through the ideas of copyright and fair use, providing context, examples, and advice. Mueller directs students through building a collection of sources and influences, leading to the development and analysis of style. With a full chapter on techniques, including approaches to exercises that are easily adapted to various approaches, media, and technologies as necessary. Two sample syllabi are included for both a semester and a quarter system.